Peran Guru Dalam Memberikan Layanan Pendidikan Bagi Anak Berkebutuhan Khusus di Sekolah Dasar - Sapitri, Eka; Inayah, Fajri; Munawaroh, Iin; R, Rendi; Aprilia, Riska; Dini, Vanda Neftria; Wulandari, Zulaikha; Pertiwi, Ratih Purnama (Madani: Jurnal Ilmiah Multidisiplin, 2024)
All citizens have the right to receive education for both normal children and children with special needs, in accordance with Law Number 20 of 2003 concerning the national education system and confirmed in National Education Minister Number 70 of 2009 concerning inclusive education for students who have disabilities and have the potential for intelligence and/or special talents, by providing opportunities for children with special needs to receive guidance at school. This research aims to describe the role of teachers in providing educational services to children with special needs, especially in individual development. This research uses a descriptive qualitative research method where data is collected through literature review. The research results show that the role of teachers in providing educational services to children with special needs is very important. This role can be seen from the teacher's assignment to provide guidance which requires teachers to be creative in developing patterns and methods of approaching children.